(3GdJLGQI GdEdcJQhfjI GdOhdjI hCKGQgG Ydi GSJNOGeGJ GdYdGeGJ GdJLGQjI (B/ s - (3eUWai ehSi MSjf GdYWjGJs; (3SejMI eUWai GdbdjhHjs; (3aGjR fYje QVhGfs; (3gGfj SQj GdOjf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2008)
(3JfGhdJ gPI GdOQGSI GdJYQV ddLhGfH GdbGfhfjI ddJLGQI GdGdcJQhfjI hNUhUG Jdc GdeJYdbI HGSJNOGe GdYdGeI GdJLGQjI GdcJQhfjI heG JQJH Ydi Pdc ef eTGcd bGfhfjI (B: (3hbO GKQfG Gf fJfGhd gPG GdehVhY ef NdGd aUd JegjOi dJhVjM eGgjI heaghe GdJLGQI GdGdcJQhfjI (B: (3hef bSefG GdHMK Gdi KdGKI GHhGH (B: (3JfGhdfG (B: (3ai GdHGH GdGhd HYV GdLhGfH GdbGfhfjI dYbhO GdJLGQI GdGdcJQhfjI PGJ GdGgejI GdNGUI cdJYGbO GdGdcJQhfis
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdJLGQj h GdHMQj, (B2008s
(3HHdjhLQGajG(B: (3UaMGJ (B439-451s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdJLGQI GdEdcJQhfjIs; (3GdYdGeGJ GdJLGQjIs; (3GdGSJNOGe GdEdcJQhfjs; (3YfGhjf GdehGbY GdEdcJQhfjIs; (3JShjI GdefGRYGJ s; (3GdefXeI GdYGdejI ddedcjI GdacQjIs; (3GdGYJOGAGJ GdEdcJQhfjIs; (3GdMeGjI GdbGfhfjI s; (3YfhGf EdcJQhfj s; (3GdSWh GdEdcJQhfjs; (3THcI GdEfJQfJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs